Formulating Rice Fields Conversion Control to Oil Palm Plantations in Tidal Wetlands of South Sumatra, Indonesia - Elisa Wildayana (Journal of Wetlands Environmental Management, 2015)
The research aimed to gain reasons of farmers to convert their rice fields, and to formulate rice fields conversion control to oil palm plantations in tidal wetlands of South Sumatra. The research was carried out in a drainage and irrigation area of Pulau Rimau, Banyuasin District South Sumatra. Collected data consists of primary and secondary data. Primary data are taken from farmers who have already converted their rice fields into oil palm plantations. Secondary data were collected from the village, the District Agriculture Office and Statistic Agency. Data was collected through the Focus Group Discussion (FGD). Data analysis was performed using Analysis Hierarchy Process (AHP) to determine the factors that influence the decision of farmers to convert their land to oil palm plantation. The research resulted that if rice yields was estimated an average 3.00 tons Milled Dry Grain (MDG)/ha, then in 2006 with the existing land could produce rice as much as 127,719 tons MDG/year, but in 2013 the productivity of agricultural land decreased to 60,138 tons MDG/year. If the predicted needs of rice in year 2006 were 50,000 tons MDG/year and increased by 75,000 tons MDG/year in 2013, then if the land use is not immediately controlled, that Pulau Rimau will deficit rice. Factors contributing to land conversion are divided into three factors, namely technical aspects, economical aspects and environment aspects. The control concept can be divided in macro concept and micro concept. The macro concept generally be only done by the government or a strong industry who pays a lot of attention to the local community. The micro concept programs can be done either by the government, private or local communities.